Studying informativity of specific IgE levels to whole cow milk allergen and its components, as well as to soy and gluten in children - N. A. Kovyazina; N. A. Alkhutova; A. V. Kamaev; O. V. Trusova; O. L. Zhizhina; M. O. Egorova (Медицинская иммунология)
Successive development of immunological tolerance to cow’s milk proteins largely depends on the timeliness and validity of the elimination diet and is most difficult in IgE-mediated food allergy. From 2012 to 2017, when examining children aged 3 months to 10 years, we found some cases with high levels of specific IgE to beta-lactoglobulin that exceeded the levels of specific IgE to the whole cow’s milk allergen (the latter is often used as a screening allergen). The aim of this study was to assess the informativity of studying the levels of specific IgE to the whole cow’s milk allergens in blood serum of children at early, preschool and primary school age. We have also included gluten (gluten) and soy as possible components of early childhood nutrition into the list of allergens under study. The study involved 100 children aged 9 months to 12 years. Clinical selection criteria included presence of anamnestic data on exacerbation of atopic dermatitis, urticaria, exacerbation of rhinitis/asthma, diarrhea, constipation or abdominal pain in response to usage of cow’s milk and/or dairy products during the last 6 months. It is shown that extended study of specific IgE levels to whole cow’s milk allergen, its components, as well as to soy and gluten, increases the accuracy of laboratory diagnostics and differential diagnosis of IgEmediated form of food allergy to cow’s milk proteins, compared with determination of serum IgE to whole cow’s milk as a screening test. A detailed study of specific IgE to milk components allowed to confirm the presence of IgE-mediated form of allergy to cow’s milk in 7% of the examined children with signs of food allergy, but in absence of specific IgE to whole cow’s milk allergen. We have also shown that in 29% of cases, the level of specific IgE to milk components was higher than those to whole cow’s milk allergen. The results of this study may be of practical importance, since the form of food allergy, as well as intensity and dynamics of reduction of production of specific IgE, are accepted criteria to forecast development of tolerance to cow’s milk proteins. In addition, identification of specific allergen (including soy bean allergen) that causes the most intense production of specific IgE, may be importance for administration of a reasonable elimination diet. The most significant allergens for diagnosis and differential diagnostics of allergy to cow’s milk in children, in addition to the “whole cow’s milk, f2” preparation, are the following allergens: “whey, f236”, “beta-lactoglobulin, f77” and “soy, f14”.